The Level of Knowledge and Skill of UTHM Engineering Lecturers on Building Information Modeling (BIM) - Ramli, Amirah Izzah; Md Noh, Ir. Dr. Mohammad Soffi (Recent Trends in Civil Engineering and Built Environment, 2022)
This research is to identify the level of knowledge and skill of Universiti Tun Hussein On Malaysia (UTHM) engineering lecturers on Building Information Modeling (BIM). BIM is a new adaptation of computer-aided technology and widely used in architecture, engineering, construction (AEC), which is replacing a 2-dimensional (2D) drawing with a 3-dimensional (3D). The application of this digital technology and construction helps the construction achieve remarkable quality and productivity changes. Today, the less personal competence in applying BIM for jobs in this industry became a major issue. According to the problem, it’s quite important for universities to teach this new technology in construction educational program. The investigation was done through a survey where 60 questionnaires were sent via internet mediums such as WhatsApp, e-mail, and google form to facilitate the data collection process and the complete questionnaire received back were analyzed with mean index and ranking method. The finding of this study shows that the level of knowledge of UTHM lecturer on BIM needs to be improved. Lack of awareness is the main challenge in implement BIM at university. Some of the recommendations, such as training programmed will be effective strategies in enhancing the level of BIM knowledge and skill of UTHM engineering lecturers.